Hi everyone. I'm in high school still so please bear with me on the simplicity of this problem. I'm working through a calculus book and the trig intro section has a proof I know to be true, but I have a hard time following in one spot. Here it is: sin^2θ=(y^2/r^2)=([r^2-x^2]/r^2)=1-(x/r)^2=1-cos^2θ The part where I get confused is how ([r^2-x^2]/r^2)=1-(x/r)^2 I would have thought the r^2/r^2 would make 1, leaving a negative x^2; thus rather than it being a 1-(x/r)^2, it would be 1-x^2. If someone could explain where my mistake is i would appreciate it. And sorry it's so messy, I couldn't figure out how to superscript so I used the ^ symbol.